MODEL ENGLISH FOR SPECIFIC PURPOSES DALAM ENGLISH BUSINESS COMMUNICATION: UPAYA GOING GLOBAL BAGI UMKM KOTA SURABAYA - Annysa Endriastuti; Maurisia Putri Permatasari (Bajang Institute, 2025)
This research examines the use of English, particularly English for Specific Purposes, in Business Communication among Micro, Small, and Medium Enterprises (MSMEs). It focuses on how these businesses improve their communication skills in international contexts, highlighting linguistic, sociolinguistic, and pragmatic aspects of communication competence. Using a descriptive qualitative method, the study employed participatory observation and interviews to assess how MSMEs interact with international partners. The findings reveal the need for English language training that emphasizes interactive and practical communication skills, essential for enhancing MSMEs' competitiveness in the global market. Ultimately, the research underscores the importance of tailored English training to foster effective communication in real-world business situations.